Memory Confidentiality and Integrity Protection Method Based on Variable Length Counter. Issue 4 (December 2014) - Haifeng, Ma; Nianmin, Yao; Shaobin, Cai; Qilong, Han
Focusing on the problem of high overhead and frequent overflow of the counter mode encryption, this paper proposed an efficient scheme to protect data confidentiality and integrity. Based on the local characteristic of data accessing, the scheme set different counter length for memory area according to different accessing frequencies and the counter length can be dynamically adjusted. The analysis and the simulation results indicated that compared with the counter mode encryption, the scheme can decrease memory space overhead and the number of overflow. The proposed scheme can be applied to other schemes of protecting confidentiality and integrity based on counters and can satisfy performance requirements for most applications.